YBCO ceramic nanofibers obtained by the new technique of solution blow spinning - Rotta, M. [UNESP] (2016)
This study proposes a novel solution blow spinning technique (SBS) for fabricating YBCO ceramic nanofibers. The precursor solutions were obtained from Y, Ba, and Cu metallic acetates (Ac) and poly(vinyl pyrrolidone) (PVP, Mw=360,000). Ac: PVP concentrations of 1:1 and 5:1 were tested, resulting in ceramic nanofibers with average diameters of 359 and 375 nm, respectively. X-ray diffraction confirmed the formation of a pure phase of YBa2Cu3O7−x. This is the first study to use SBS for fabricating YBCO nanofibers, and this technique shows promise for obtaining high-quality ceramic materials.